Kajian Problematika Perkembangan Perusahaan Modal Ventura Syariah di Indonesia - Fithri, Windy Dwi Zhelsa; Arifin, Sirajul (ITB AAS INDONESIA Surakarta, 2023)
This study aims to review the problematic existence and resolution of Islamic venture capital companies in Indonesia. Nowadays, along with the rapid development of the Islamic financial industry, venture capital companies are also developing with the existence of Islamic venture capital companies that apply sharia principles. Islamic venture capital companies have a market share of Muslim entrepreneurs who want to do financing in accordance with Islamic provisions. However, in practice, the Islamic venture capital industry still encounters several obstacles that require new resolutions to overcome them. This study is a literature survey. This research identifies several issues plaguing the venture capital sector. The success of the venture capital sector is still highly reliant on external factors; the Islamic venture capital sector, for example, has a business model that frequently incorporates the notion of profit sharing. The Islamic venture capital sector is risky because of poor literacy and few human resources. So that the resolutions that can be done include: Support for literacy, support for long-term access and support for establishing a deposit insurance agency (LPS).